20 jaar grafiek : Koninklijke Academie voor Schone Kunsten Gent. (Gent : Koninklijke Academie voor Schone Kunsten, 1992)
Decq, Frank ; Dendooven, Gerda ; Dobbelaere, Danny ; Fink, Christoph ; Frans + Frank ; Morrens, Peter ; Vandendriessche, Herbert ; Zoete, Dirk
boek